Measurement of Beauty in Architecture - Kharrufa, Sahar Naieeb (Iraqi Journal of Architecture and Planning, 2009)
Several years ago an attempt was made to measure the beauty of the architectural design. The objective was to prepare the design for evaluation by a computer. It was found that such measurement was very complicated and requires much more research. Several more attempts were made to fill in ih" gup. but the total picture remained unclear. This paper attempts to draw a map for futuri work. The object of beauty in architecture depends on content and form. Content includes function and symbol. But the subject is complicated by the fact that beauty is subjective and changes according to viewer, time, and place.